Frontier crucible [videorecording (DVD)] - Clohessy, Myles; Stickley, Mary; Brown, Eli, 1999-; Masson, Ryan; Holtz, Zane, 1987-; Spears, Eddie; Hammer, Armie, 1986-; Macy, William H., 1950-; Jane, Thomas; Whittington, Harry, 1915-1989 (Well Go USA Entertainment, 2026)
In 1874, on the harsh frontier of the Arizona landscape, a former soldier is sent alone on a dangerous mission to deliver a wagon full of precious medical supplies through the hostile Apache territory. When he encounters a stranded trio of dangerous outlaws and a desperate young couple, he is thrown into an uneasy alliance of mutual need and fraying trust. In a land where survival is the only rule, all bets are off when every decision means life or death.